Alterações morfofisiológicas por estímulo mecânico e químico em mudas de Cordia trichotoma Vell. Arrad. ex. Steuds e Guazuma ulmifolia Lamarck - Ajala, Michelle Cristina (2015)
The last phase of seedling production, the hardening is a technique used in nurseries which aims to expose the seedlings to more severe conditions than those submitted in the growth phase, in order to prepare them for the field. Based on the above, the aim of the present study was to evaluate the effect of the application of ethylene and bending stem in two native forest species (at different times) Cordia trichotoma and Guazuma ulmifolia. The treatments consisted in the application of stem pushups 0, 10, 20 and 40 daily crunches and sprays (0 to 4) with ethylene in a factorial design in two native species. Thus, this study was subdivided into three parts. In the first part were evaluated morphological parameters of the seedlings and their survival. The variables were height of the aerial part of the plant, stem diameter, number of leaves, SPAD index and dry mass of seedlings. In the second part, we evaluated the concentration of soluble carbohydrates in leaves, cell damage through the loss of root electrolytes and the lignin content in stems of both species. In the third part evaluated the concentration of macronutrients N, P, K, Ca and Mg. The evaluated morphological parameters was found that the G.ulmifolia species decreased in the increase in height of more than 60% and 35% in diameter collect when subjected to bending stem compared to control seedlings. The most significant results occurred with 20 pushups shoot. C. trichotoma a significant decrease in the increase in height, and the application of these factors together decreased the survival of the species. In physiological parameters G. ulmifolia species showed a linear reduction in the lignin content and increased loss of electrolytes root (REL) when subjected to bending. The concentration of carbohydrates increased by 55% when combined with stem bending factors and spraying with ethylene. The species C. trichotoma there was a reduction in the concentration of lignin, REL and carbohydrates (with the application of stem crunches and spraying with ethylene). Concerning macronutrients, it was found to be reduced to N concentration (13.2%) and P (20%) in G. ulmifolia stems, while K increased with up to 23 ethylene flexing when applied. The concentration of Ca and Mg showed an increase with 26 pushups shoot. Since the application ethylene concentration decreased by 21.6% and 14% for calcium and magnesium G. ulmifolia respectively. The species C. trichotoma revealed a linear increase in the concentration of N in stems of seedlings mechanically stimulated and sprayed with ethylene. In roots, the increase was 45% flexed 10 times a day with ethylene seedlings application. The calcium content was reduced in the stems and roots when compared to control seedlings in both treatments stem and ethylene flexing C. trichotoma. The magnesium concentration was high in no spray seedlings with ethylene until stem 25 flexing while plants sprayed linearly reduced Mg concentration is increased as the stem flexing in said species